2009
DOI: 10.1002/nla.640
|View full text |Cite
|
Sign up to set email alerts
|

Backward perturbation analysis for scaled total least‐squares problems

Abstract: The scaled total least-squares (STLS) method unifies the ordinary least-squares (OLS), the total leastsquares (TLS), and the data least-squares (DLS) methods. In this paper we perform a backward perturbation analysis of the STLS problem. This also unifies the backward perturbation analyses of the OLS, TLS and DLS problems. We derive an expression for an extended minimal backward error of the STLS problem. This is an asymptotically tight lower bound on the true minimal backward error. If the given approximate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…It can easily be shown that µ = 0 if and only if x =x; see, e.g., [5,Corollary 3.1]. Thus as long as x =x, the matrix M in (2.2) has full column rank and σ min (M ) > 0.…”
mentioning
confidence: 99%
“…It can easily be shown that µ = 0 if and only if x =x; see, e.g., [5,Corollary 3.1]. Thus as long as x =x, the matrix M in (2.2) has full column rank and σ min (M ) > 0.…”
mentioning
confidence: 99%
“…Suppose y is an approximate solution of the STLS problem . Chang and Titley‐Peloquin prove that y is the exact STLS solution for the data set [ A + E , b + f ] if and only if [ E , f ] is in the set ϵAMathClass-punc,b(γ)MathClass-rel={[EMathClass-punc,f]|}falsefalsearrayarrayleftMathClass-open(A+EMathClass-close)TMathClass-open[b+fMathClass-open(A+EMathClass-close)yMathClass-close]=b+fMathClass-open(A+EMathClass-close)y2γ2+y2y,arrayleftb+fMathClass-open(A+EMathClass-close)y2γ2+y2<σmin2MathClass-open(A+EMathClass-close)MathClass-punc.…”
Section: Backward Error For the Scaled Total Least Squares Problemmentioning
confidence: 99%
“…Chang and Titley‐Peloquin derive an expression for the extended backward error of the scaled total least squares (STLS) problem, which is an asymptotically tight lower bound on the true backward error. Furthermore, several results on the backward error results of OLS, the data least squares (DLS), and the total least squares (TLS) are then obtained from the backward error results for STLS in .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations